Effectiveness of Sterilization Methods of Coffee Leaf Explants (Coffea canephora Var. Milo Pace) To Decrease Contamination and Browning In Vitro - Kusbianto, Dwi Erwin; Irsyadi, Muhammad Burhanuddin; Hasanah, Rizky; Az-Zahra, Rana (Journal of Soilscape and Agriculture, 2025)
Coffee is one of the leading plantation commodities that are in demand by the public. Robusta coffee var. Milo Pace is Jember's flagship local coffee that was only released at the end of 2023. Seedling propagation continues to be pursued to preserve the coffee. In vitro culture is one of the effective plant propagation methods for production in large quantities. However, explant sterilization is a crucial stage in in vitro culture. Reports related to in vitro culture of robusta milo pace have never been reported before. Therefore, optimization of sterilization methods is the initial stage in supporting the success of in vitro culture of robusta milo pace coffee. The purpose of this study was to obtain the optimal method of sterilization of leaf explants of robusta milo pace coffee. This study used a one-factor randomized design, namely the method of sterilization of coffee leaf explants consisting of 12 methods. The sterilants used were detergent, bactericide, fungicide, NaOCl, H2O2, alcohol and distilled water with different time and concentration. The results showed that sterilization of explants by method XII with 2 g/L detergent for 20 minutes, 2 g/L bactericide and 2 g/L fungicide for 60 minutes, 1.05% NaOCl for 15 minutes, 0.525% NaOCl 10 minutes and 1.5% H2O2 can suppress 20% contamination such as fungi and bacteria with an average contaminant appearance time of 11 days after inoculation. The percentage of browning was 20% with an average appearance of 8.8 days after inoculation. This method maintains the percentage of live explants up to 60% characterized by fresh green explants.